Loss of 2 Akt (Protein Kinase B) Isoforms in Hematopoietic Cells Diminished Monocyte and Macrophage Survival and Reduces Atherosclerosis in Ldl Receptor-Null Mice. Issue 2 (February 2019) - Babaev, Vladimir R.; Ding, Lei; Zhang, Youmin; May, James M.; Ramsey, Stephen A.; Vickers, Kasey C.; Linton, MacRae F.
Abstract : Objective—: Macrophages express 3 Akt (protein kinase B) isoforms, Akt1, Akt2, and Akt3, which display isoform-specific functions but may be redundant in terms of Akt survival signaling. We hypothesize that loss of 2 Akt isoforms in macrophages will suppress their ability to survive and modulate the development of atherosclerosis. Approach and Results—: To test this hypothesis, we reconstituted male Ldlr −/− mice with double Akt2/Akt3 knockout hematopoietic cells expressing only the Akt1 isoform (Akt1 only ). There were no differences in body weight and plasma lipid levels between the groups after 8 weeks of the Western diet; however, Akt1 only → Ldlr −/− mice developed smaller (57.6% reduction) atherosclerotic lesions with more apoptotic macrophages than control mice transplanted with WT (wild type) cells. Next, male and female Ldlr −/− mice were reconstituted with double Akt1/Akt2 knockout hematopoietic cells expressing the Akt3 isoform (Akt3 only ). Female and male Akt3 only → Ldlr −/− recipients had significantly smaller (61% and 41%, respectively) lesions than the control WT→ Ldlr −/− mice. Loss of 2 Akt isoforms in hematopoietic cells resulted in markedly diminished levels of white blood cells, B cells, and monocytes and compromised viability of monocytes and peritoneal macrophages compared with WT cells. In response to lipopolysaccharides, macrophages with a single Akt isoform expressed low levels of inflammatory cytokines; however, Akt1 only macrophages were distinct in expressing high levels of antiapoptotic Il10 compared with WT and Akt3 only cells. Conclusions—: Loss of 2 Akt isoforms in hematopoietic cells, preserving only a single Akt1 or Akt3 isoform, markedly compromises monocyte and macrophage viability and diminishes early atherosclerosis in Ldlr −/− mice. Abstract : Supplemental Digital Content is available in the text.